Renal artery thrombosis in COVID-19. (2020) - Acharya, Sudeep; Anwar, Shamsuddin; Siddiqui, Fasih Sami; Shabih, Sohaib; Manchandani, Umesh; Dalezman, Solomon
Abstract: COVID-19 has been described to have association with hypercoagulable state and thromboembolic events in major blood vessels, pulmonary artery, major limb vessels causing limb ischemia. associated with neurological symptoms and complications including stroke. We present a unique case of renal artery thrombus formation secondary to COVID-19. To the best of our knowledge this is the fourth manuscript describing renal artery thrombosis with evidence on imaging studies in medical literature.